Sexual Dysfunctions Special Issues - Goshtasebi, Azita (IntechOpen, 2011)
Sexual dysfunctions have recently recognized as one of the major public health problems. This book enhances our scientific understanding of sexual function and dysfunction from different perspectives. It presents evidence-based interventions for sexual dysfunctions in difficult medical situations such as cancer, and gives a valuable overview of recent experimental researches on the topic. Published in collaboration with InTech - Open Access Publisher, this imperative work will be a practical resource for health care providers and researchers who are involved in the study of sexual health.